2018
DOI: 10.1093/brain/awx375
|View full text |Cite
|
Sign up to set email alerts
|

HDAC6 is a therapeutic target in mutant GARS-induced Charcot-Marie-Tooth disease

Abstract: Patients with Charcot-Marie-Tooth disease with predominant axonal loss (CMT2) show extensive genetic heterogeneity. Benoy et al. demonstrate a link between CMT2 and histone deacetylase 6 (HDAC6), which controls the acetylation of α-tubulin, and propose that pharmacological inhibition of HDAC6 has therapeutic potential in CMT2 genetic variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
120
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(129 citation statements)
references
References 54 publications
9
120
0
Order By: Relevance
“…Deficits in axonal transport contribute to many different genetic neuropathies (Prior et al, 2017;Beijer et al, 2019), and its early involvement in disease may be a common driver in peripheral nerve selectivity typical of many forms of CMT2. Indeed, disruption of long-range trafficking has been identified in sensory neurons cultured from CMT2D DRG (Benoy et al, 2018;Mo et al, 2018). Contrastingly, we found no difference in retrograde transport of signalling endosomes between wild-type and Gars C201R/+ at one and three months of age (Figure 4 and Supplementary Figure S3).…”
Section: Long-range Transport Is Not Universally Impaired In Cmt2d Sementioning
confidence: 64%
See 2 more Smart Citations
“…Deficits in axonal transport contribute to many different genetic neuropathies (Prior et al, 2017;Beijer et al, 2019), and its early involvement in disease may be a common driver in peripheral nerve selectivity typical of many forms of CMT2. Indeed, disruption of long-range trafficking has been identified in sensory neurons cultured from CMT2D DRG (Benoy et al, 2018;Mo et al, 2018). Contrastingly, we found no difference in retrograde transport of signalling endosomes between wild-type and Gars C201R/+ at one and three months of age (Figure 4 and Supplementary Figure S3).…”
Section: Long-range Transport Is Not Universally Impaired In Cmt2d Sementioning
confidence: 64%
“…Pre-symptomatic disturbances in axonal trafficking are thought to underlie, or at least contribute to, several neurological diseases (Sleigh et al, 2019). Indeed, primary DRG neurons cultured from 12 day old Gars Nmf249/+ mice display reduced retrograde transport speeds of nerve growth factor (NGF)-loaded endosomes (Mo et al, 2018), while reduced mitochondrial motility was also identified in sensory processes of 12 month old Gars C201R/+ mice (Benoy et al, 2018). Disruption of two different cargoes suggests a broad transport impairment (e.g.…”
Section: Long-range Signalling Endosome Transport Is Unaffected In CMmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, two genetics experiments in flies and mice have demonstrated that dominant mutations in GARS cause CMT through toxic gain-of-function effects [10,18]. Several binding partner of CMT mutants have been discovered, including Nrp1 [25], Trk [26] and HDAC6 [27,28]. Here we presented that SIRT2, the acetylated tubulin deacetylase, is able to bind tightly with wildtype GARS comparing with CMT mutants, we didn't rule out the possibility that CMT mutants might gain the functions to increase deacetylation activity of SIRT2 which leading to decrease the acetylated tubulin.…”
Section: Disscussionmentioning
confidence: 99%
“…Therefore, mutations that weaken INF2 binding to the CAP/KAc-actin inhibitory complex may lead to disease through increased INF2 activity. Interestingly, recent studies have shown that aberrant HDAC6 activity can also lead to CMTD [75][76][77] , raising the possibility of another route for INF2 activation in this disease. Overall, our study provides a framework for understanding both actin regulation and disease progression in a new way.…”
Section: Inf2 Regulation and Human Diseasementioning
confidence: 99%